Neuro-linguistic programming in the teaching-learning process of English as a foreign language - Author; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Currently, the requirements for learning foreign languages are very high, one of the tasks faced by teachers is to cultivate the communication skills of students. There is insufficient application of emerging techniques based on Neuro-Linguistic Programming or known by its acronym as NLP in the teaching of the English language. The use of various techniques can provide you with new learning opportunities, so the objective of this research is to identify how the application of techniques from Neuro-Linguistic Programming as a methodology influences the process of teaching English as a foreign language. The application of techniques that NLP offers, arises from the need to implement new strategies and tools that help improve the educational process. In addition, it offers a general description of what Neurolinguistic Programming is, its beginnings, where it comes from, how it works, in that context, it seeks to provide information on how these techniques help teachers to improve the quality of teaching. The research was qualitative in nature and involved the collection and analysis of non-numerical data found in texts and videos to understand concepts, opinions or experiences, for the review of documents the method of documentary bibliographic review (Desk research) of an analytical type was used. It can be concluded that Neurolinguistic Programming works in favor of the improvement and acquisition of the language, since it encourages the teacher in the application of techniques, which serve as strategies and tools, for the improvement of the cognitive process and taking as a base in turn the multiple intelligences of individuals to activate learning.